PENGARUH STRUKTUR KEPEMILIKAN TERHADAP NILAI PERUSAHAAN DENGAN EFISIENSI STRUKTUR MODAL SEBAGAI VARIABEL MEDIASI - Felicia Wuisan; Excel Limbunan; Oktavianus Pasoloran; Cherly Thanamal (Magister Akuntansi, Universitas Atma Jaya Makassar, 2021)
This study aims to examine the influence of ownership structure on firm value mediated by efficiency capital structure. This research uses pecking order theory, agency theory, and stakeholder theory. The population used in this study are all companies listed on the Indonesia Stock Exchange (IDX) with the research period of 2016-2018. The method of determining the sample using non-random sampling i.e purposive sampling and uses secondary data in the form of annual reports and financial statements of the company. The analytical method used are path analysis and sobel test. The results showed that the efficiency of capital structure can fully mediate the effect of ownership structure on firm value.